Studies on the reproductive biology of white yam (Dioscorea rotundata Poir.) - Segnou, M.; Fatokun, C.; Akoroda, M.O.; Hahn, S. (1992)
Investigations were conducted on the identification and distribution of yam natural pollinators, flowering pattern and hybridization of white yam (Dioscorea rotundata Poir.) at the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria, in order to provide informations for producing hybrid seeds needed for vam genetic improvement. Insects belonging to the oleoptera (48.0%), Diptera (20.4%), Hymenoptera (20.0%), Hemiptera (5.8%), and Thysanoptera (5.8%) were caught around yam plants and presumed to be pollinators: they entered open-receptive-flowers and their presence on yam plants coincided with the duration of the flowering period. Studies on the flowering pattern revealed that: (i) Male and female clones differed in their periods of flower initiation as well as the flowering duration; (ii) Seed production and conventional breeding methods are feasible if staggered planting, water and soil fertility could be managed to ensure that flowering periods of males and females nick and also extend flowering. Artificial pollinations within white yam and between white yam and yellow yam (D. cayenensis Lam) using the camel hair brush method were successful, but resulted in a relatively low fruit set (31.8% maximum). This method was more effective than natural pollination (19.2%) and can thus supplement it for the production of hybrid seeds for introducing genetic variation in yam breeding populations.